Impact of hypertension on retinal capillary microvasculature using optical coherence tomographic angiography. Issue 3 (March 2019) - Chua, Jacqueline; Chin, Calvin Woon Loong; Hong, Jimmy; Chee, Miao Li; Le, Thu-Thao; Ting, Daniel Shu Wei; Wong, Tien Yin; Schmetterer, Leopold
Abstract : Objective: Reduction in capillary density or rarefaction is a hallmark of essential hypertension. We measured the retinal capillary density using noninvasive optical coherence tomographic angiography (OCT-A) in adults with treated systemic hypertension and determined possible correlations with ambulatory blood pressure (BP) and renal parameters. Methods: This observational cross-sectional study consisted of 153 normal eyes from 77 nondiabetic hypertensive adults [mean (SD) age, 58 (9) years; 49% women; 23% poorly controlled BP]. Data on 24-h ambulatory BP monitoring, serum creatinine, and urine microalbumin/creatinine ratio (MCR) were collected. Estimated glomerular filtration rate (eGFR) was calculated based on CKD-EPI Creatinine Equation. Retinal capillary density measured with the OCT-A (AngioVue) at superficial (SVP) and deep vascular plexuses (DVP). Linear regression was used to investigate the association of risk factors with capillary density. Results: Retinal capillary density (percentage) at DVP was reduced in patients with poorly controlled BP (SBP = 148 ± 8 mmHg; 27.2 ± 13.0) compared with those with well controlled BP (SBP = 125 ± 9 mmHg; 34.7 ± 11.3). In the multivariable analysis, poorly controlled BP [ β  = −6.49, 95% confidence interval (CI), −12.39 to −0.59], higher SBP ( β  = −0.23, 95% CI −0.44 to −0.02) and lower eGFR ( β  = 6.42, 95% CI 1.25–11.60) were associated with sparser retinal capillary density. Systemic factors were not associated with capillary density at SVP (all P  > 0.05). Conclusion: In adults with treated systemic hypertension, retinal capillary density reduced with higher BP and poorer eGFR. These findings highlight the potential role of OCT-A to study early microvascular changes because of systemic hypertension.